1994
DOI: 10.1007/bf00588073
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysm associated with pituitary adenoma shown by MR angiography: case report

Abstract: We present a case of aneurysm of the anterior communicating artery associated with a pituitary adenoma. Recognition of this association has important clinical implications, leading to modification of the surgical approach. The aneurysm was shown on MR angiography and confirmed with contrast arteriography and at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Infact several authors have reported on subarachnoid haemorrhage during transphenoidal surgery for pituitary adenomas, due to accidental damage to previously undetected intracranial aneurysms [ 15 – 17 ]. Some authors recommend routine preoperative carotid artery angiography in all patients with pituitary macroadenomas before trans-sphenoidal surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infact several authors have reported on subarachnoid haemorrhage during transphenoidal surgery for pituitary adenomas, due to accidental damage to previously undetected intracranial aneurysms [ 15 – 17 ]. Some authors recommend routine preoperative carotid artery angiography in all patients with pituitary macroadenomas before trans-sphenoidal surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unii autori preferă rezolvarea acestora în două etape pe când alții într-o etapă. De preferință este a doua, pentru a reduce maximal posibil complicațiile legate de intervenții, durata spitalizării, dar evident cu analiza minuțioasă a particularităților patologiei pacientului [6,7]. Accesul pterional clasic este unul din cel mai recomandat, care oferă cel mai bun rezultat posto-Figura1.…”
Section: Introducereunclassified
“…If the AComA is involved in vascular anomalies such as cerebral aneurysms, AComA descent might result in vascular complications during or after TSS, which are life-threatening consequences. [ 1 3 5 6 9 11 12 13 ] Vascular complications during and after TSS are the result of abrupt tumor capsule collapse into the sella turcica following adenoma removal, which may cause traction of the AComA. [ 9 13 ]…”
Section: Introductionmentioning
confidence: 99%